2022
DOI: 10.9734/ijecc/2022/v12i111346
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Varieties of Broccoli (Brassica oleracea var. italica) under Prayagraj Agro-climatic Condition

Abstract: A study entitled “Performance of different varieties of broccoli (Brassica oleracea var. italica) under Prayagraj agro-climatic condition” was carried out at crop Vegetable Research Farm, Department of Horticulture, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj (Allahabad), U. P. during academic session 2021-22. The experiment consists of   7 Varieties in 3 replications. The result showed that there were significant differences found among all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…This might be due to continuous application of organic inputs such as vermicompost, waste decomposer, bio fertilizers and plant cake thus improves the soil fertility status and it is also stated that vermicompost has higher N availability and the supply of several other plant nutrients such as phosphorus (P), potassium (K) and sulphur (S) were significantly increased by adding vermicompost as compared to conventional farming in the same soil. This is in accordance with the findings of Anjana Thakur et al [1], Gayathri et al [2] and Richa N and Baburam K [3] In addition to that application of panchagavya at regular intervals has resulted higher microbial population around the root zone. This may be attributed to the fact that panchagavya is a rich source of beneficial microorganisms like N-fixers and P-solubilizers which in turn increases the soil nutrient status.…”
Section: Resultssupporting
confidence: 92%
“…This might be due to continuous application of organic inputs such as vermicompost, waste decomposer, bio fertilizers and plant cake thus improves the soil fertility status and it is also stated that vermicompost has higher N availability and the supply of several other plant nutrients such as phosphorus (P), potassium (K) and sulphur (S) were significantly increased by adding vermicompost as compared to conventional farming in the same soil. This is in accordance with the findings of Anjana Thakur et al [1], Gayathri et al [2] and Richa N and Baburam K [3] In addition to that application of panchagavya at regular intervals has resulted higher microbial population around the root zone. This may be attributed to the fact that panchagavya is a rich source of beneficial microorganisms like N-fixers and P-solubilizers which in turn increases the soil nutrient status.…”
Section: Resultssupporting
confidence: 92%
“…Sivakumar et al (2022) found the significant response among broccoli varieties on plant height. Similar results were recorded by Tejaswini et al (2018), Prashanthi et al (2022) as well as Thakur et al (2016). Some varieties recorded the lowest plant height that might be due to its inherent genotypic configuration (Thapa and Rai, 2012).…”
Section: Plant Height (Cm)supporting
confidence: 82%
“…Similarly, at 35 DAT, the maximum number of leaves (7.50) was produced by Calabrese while the minimum was found in Centauro. Prashanthi et al (2022) observed similar differences among varieties in number of leaves which may be due to the variation in their inherent genetic capacity. Varieties adapted to different environmental conditions may exhibit variations in leaf number.…”
Section: Number Of Leaves Per Plantmentioning
confidence: 76%
See 1 more Smart Citation
“…Different varieties of vegetable typically may show differences in nutrient value, antioxidant content, and mineral content. For instance, a study of the different varieties of broccoli showed that their quality indices differ significantly [ 24 , 25 ]. Meanwhile, many of the published studies on cabbage quality mainly focused on the influence of different cultivation conditions and seasons on nutritional quality and only considered a few cabbage varieties, making the results of these studies difficult to compare.…”
Section: Introductionmentioning
confidence: 99%